Supervision and professional development in in-service teacher training regarding sexuality education - Vilaça, Teresa (2011)
This research describes the contributions for teachers’ professional development of two different in-service teacher training modalities, a Workshop and a Training Course, involving, respectively, eight (n=128) and seven (n=130) different classes, whose principal aim was to prepare teachers to carry out action-oriented sexuality education projects in their schools. The content analysis of materials produced during the in-service teacher training, complemented with a semi-structured individual interview, and observation, associated with a focus-group interview were selected as research techniques for the triangulation of data. Principal results showed some differences in teachers’ professional development who attended these different training modalities. A larger number of teachers who attended the Workshop than those involved in the Training Course, developed reflexive actions which led to positive changes in their methodological approaches of sexuality education and increased more student participation. This article concludes by discussing the influence of these results with regards to the selection of the modality of in-service teacher training when personal and professional development is intended.